PSIKOANALISIS SIGMUND FREUD PADA ANTOLOGI CERPEN KARYA SENO GUMIRA AJIDARMA - Mhd. Anggie Januarsyah Daulay (BAHAS, 2016)
The purpose of this research is to describe character’s personality structures in anthology short story “’Aku Kesepian, Sayang.’, ‘Datanglah, Menjelang Kematian.’” Made by Seno Gumira Ajidarma. The personality structures consist of id (desire and needs), ego (distribution), and superego (balancer/control/normative). This research’s analysis used personality structures theory in study of psychoanalysis by Sigmund Freud. The source of data in this research consists of three short stories, such as “’Aku Kesepian, Sayang.’, ’Datanglah, Menjelang Kematian.’”, ”Legenda Wongasu” and ”Penjaga Malam dan Tiang Listrik”. Each of these short stories has one main character. The collected data consist of sentences and paragraphs which collected from the techniques of character’s establishment in literature. The result of research showed (1) “’Aku Kesepian, Sayang.’, ’Datanglah, Menjelang Kematian’” short stories used two technique, discourse and feeling and thought technique, (2) “Lengenda Wongasu” short story used one technique, character’s response technique, (3) “Penjaga Malam dan Tiang Listrik” short story used two techniques, such as discourse/other characters’ response technique and character’s response technique. The result of personality structure research consist of id, ego, and superego that main characters’ experienced, make two final result, such as superego successfully work (positive) and superego does not work. The two of short stories which have the superego (positive) personality character that parallel with the final function as normative are ”’Aku Kesepian, Sayang.’, ’Datanglah, Menjelang Kematian.’”, ”Legenda Wongasu”, Whereas one short story which has negatif superego of personality character is”Penjaga Malam dan Tiang Listrik”   Keywords: psychoanalysis: personality structure, character